Kemala Sari, SE, MM - Harnita, Harnita; Taqwa, M.Si, Salma; Kemala Sari, SE, MM, Mareta (Pendidikan Ekonomi, 2014)
ABSTRACTTop of Form             Issues that are examined in this study is whether there are significant internal control and appropriateness of the compensation to the tendency of the accounting fraud at. Igasar ( cement desert group) aims to determine : 1 ) the influence of internal controls over the accounting fraud 2 ) the effect of conformity tendency compensation to accounting fraud at PT Igasar ( Semen Padang ) . This type of research is a quantitative study with a location at Jl . Indarung Comp . Semen Padang , with a population of 35 people and a total sampling technique using sampling and sample saturated.             The results showed that : 1 ) internal control significant effect on the tendency of the accounting fraud by the regression coefficient of 0.296 with significant ( 0.008 < 0.05 ) , meaning that if the internal controls increased by one unit , then the tendency of accounting fraud increased by 0,296 units . In other words , the existing internal control system will not be able to suppress the practice of accounting fraud . 2 ) There is a significant relationship between the suitability of compensation to the tendency of the accounting fraud by a coefficient of 0.327 , meaning that the suitability of compensation increases when the accounting fraud to increase one unit of the regression coefficient increased by 0.327 units with Sig 0.000 < 0.05 . Improved internal controls and accounting fraud accounting fraud did not result in decreased due to the influence of accounting fraud is influenced by other factors Keywords : Internal Control , Compliance Compensation , Accounting Fraud Trends               Pokok persoalan yang dikaji dalam penelitian ini adalah apakah terdapat pengaruh pengendalian internal dan kesesuaian kompensasi terhadap kecenderungan kecurangan akuntansi pada PT. Igasar (semen padang group) ini bertujuan untuk mengetahui : 1) pengaruh pengendalian internal terhadap kecurangan akuntansi  2) pengaruh kesesuaian kompensasi terhadap kecenderungan kecurangan akuntansi pada PT Igasar (Semen Padang). Jenis penelitian yang digunakan adalah penelitian Kuantitatif dengan lokasi di Jl. Indarung Komp. Semen Padang, dengan populasi sebanyak 35 orang dan teknik pengambilan sampel menggunakan total sampling dan sampel jenuh.             Hasil penelitian menunjukkan bahwa : 1) pengendalian internal berpengaruh signifikan terhadap kecenderungan kecurangan akuntansi dengan koefisien regresi sebesar 0,296 dengan signifikan (0,008 < 0,05), artinya jika pengendalian internal mengalami peningkatan sebesar satu satuan, maka kecenderungan kecurangan akuntansi bertambah sebanyak 0,296 satuan. Dengan kata lain, sistem pengendalian internal yang ada tidak akan mampu menekan terjadinya praktek kecurangan akuntansi. 2) Terdapat pengaruh yang signifikan antara kesesuaian kompensasi terhadap kecenderungan kecurangan akuntansi dengan koefisien sebesar 0,327, artinya  apabila kesesuaian kompensasi meningkat kecurangan akuntansi meningkat satu satuan maka koefisien regresi meningkat sebesar 0,327 satuan dengan Sig 0,000 < 0,05. Peningkatan pengendalian internal dan kecurangan akuntansi tidak mengakibatkan kecurangan akuntansi menurun karena untuk mempengaruhi kecurangan akuntansi dipengaruhi oleh faktor lain